HLADR: a database system for enhancing the discovery of biomarkers for predicting human leukocyte antigen-mediated idiosyncratic adverse drug reactions. (November 2015) - Du, Tingting; Yang, Lun; Luo, Heng; Zhou, Peng; Mei, Hu; Xuan, Jiekun; Xing, Qinghe; Ning, Baitang; Mendrick, Donna L; Shi, Leming
Aim: To establish a database for the associations between idiosyncratic drug reactions (IDRs) and human leukocyte antigens (HLAs) and to systematically assess the characteristics of the drug–HLA associations.Materials & methods: Electronic databases were searched to extensively identify drug–HLA association studies from 1966 to present.Results: A drug-HLA-IDR database, HLADR, was created. The drug–HLA relationship network clearly reflected an ethnicity dependency of the associations. The positive predictive values and the negative predictive values demonstrated that other potential factors may also regulate the occurrence of HLA-specific IDRs.Conclusions: Constructing studies with samples from homogeneous ethnic groups and identifying cofactors that affect negative predictive values and positive predictive values will become necessary to enhance the predictability of HLA biomarkers for future research on IDRs.